2021
DOI: 10.1590/s0004-2803.202100000-84
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Irritable Bowel Syndrome Symptoms and Fodmaps Intake in University Students

Abstract: BACKGROUND: Irritable bowel syndrome (IBS) symptoms such as diarrhea, bloating and abdominal pain can reduce University student’s productivity and learning ability. One of the possible treatments for IBS is the temporarily exclusion of foods that have a high content of short-chain fermentable carbohydrates, the fermentable, oligosaccharides, disaccharides, monosaccharides and polyols (FODMAPs). OBJECTIVE: This study aimed to assess University student’s intake of foods that are rich in FODMAPs, looking for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Uncontrolled observations have suggested efficacy of the FODMAP diet in Central America 91 and association of high FODMAP foods with symptoms have been made in South America. 92 It does appear that the moderate intake of FODMAPs (sufficient to enable the benefits of their restriction to manifest) stretches across most cultures, with the exception of Japan where efficacy of the diet has yet to be reported, and an association study of perceptions of the relationship of specific food intake and lower GI symptoms suggested that FODMAPs were not a problem, although such interpretation of the findings was highly speculative. 93 Despite evidence revealing its efficacy, there are challenges in implementing the FODMAP diet into different cultures.…”
Section: Culturally-appropriate Fodmap Dietsmentioning
confidence: 99%
“…Uncontrolled observations have suggested efficacy of the FODMAP diet in Central America 91 and association of high FODMAP foods with symptoms have been made in South America. 92 It does appear that the moderate intake of FODMAPs (sufficient to enable the benefits of their restriction to manifest) stretches across most cultures, with the exception of Japan where efficacy of the diet has yet to be reported, and an association study of perceptions of the relationship of specific food intake and lower GI symptoms suggested that FODMAPs were not a problem, although such interpretation of the findings was highly speculative. 93 Despite evidence revealing its efficacy, there are challenges in implementing the FODMAP diet into different cultures.…”
Section: Culturally-appropriate Fodmap Dietsmentioning
confidence: 99%
“…The results of the present study provide preliminary scientific evidence that IBS is very common in human medicine students, thereby offering a consistent analysis for implementing preventive measures. For example, encouraging improvements in lifestyle, reinforcing participation in sports activities to reduce the constant stress experienced during university life (44,45), or employing educational talks on nutrition such as the use of a low FODMAP diet (46) or consuming a diet richer in proteins, as it acts as a protective factor for IBS (47). All the aforementioned have had a positive effect on IBS, aiming to prevent its progression and/or severity (46).…”
Section: Relevance Of Findings In Public Healthmentioning
confidence: 99%
“…For example, encouraging improvements in lifestyle, reinforcing participation in sports activities to reduce the constant stress experienced during university life (44,45), or employing educational talks on nutrition such as the use of a low FODMAP diet (46) or consuming a diet richer in proteins, as it acts as a protective factor for IBS (47). All the aforementioned have had a positive effect on IBS, aiming to prevent its progression and/or severity (46). This would seek to avoid economic expenses for medical treatment and also to achieve optimal academic learning.…”
Section: Relevance Of Findings In Public Healthmentioning
confidence: 99%
“…However, FODMAP consumption has been shown to induce symptoms in IBS sufferers [21], perhaps explaining why a large population-based cohort study from France found that FODMAP intake was lower in IBS subjects than in the general population and intake decreased as IBS severity increased [22]; IBS sufferers had, presumably, and either consciously or unconsciously, learned to avoid these offending foods; yet another factor that may confound the interpretation of clinical trials.…”
Section: Key Pointsmentioning
confidence: 99%